The Impact of the Nonprofit Sector on Employment and Unemployment in Developed Economies: Dynamic Panel Data Analysis - Gülçin Kaya İnceiplik; Halil Tunalı (Sosyal Siyaset Konferansları Dergisi)
In the last quarter of the last century, the reshaping of the state apparatus under the domination of liberal economics and globalization led to a rapid and radical transformation of the nonprofit sector. With growing incomes, expenditures, staff and volunteers, these organizations have become major economic actors in many countries today. Indeed, economic research and technical reports on the sector have started to attract attention in the last few decades. When we look at these studies, we can say that the sector has a very active presence in labor markets, especially in developed countries. However, these studies do not econometrically evaluate the direction and extent to which the sector actually affects employment in countries. Therefore, the subject of this study was to investigate the data set of the 16 developed countries for the period of 2008 to 2018 using the least squares dummy variable corrected estimator. It was observed that there is a positive relationship between the employment rate and the gross value added of nonprofit organizations, and there is no statistically significant relationship between the employment rate and the world giving index. In addition, a negative relationship was found between the unemployment rate and the gross value added of nonprofit organizations and the world giving index.